Faktor-Faktor Yang Mempengaruhi Minat Pembeli Kain Tenun di Desa Sukarara Kecamatan Jonggat Kabupaten Lombok Tengah - Muhammad Habibullah Aminy (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
Every company is required to be ready to face increasingly fierce business competition. In business competition, the requirement for a company to succeed and succeed is to try to achieve goals by creating and retaining consumers, many factors that affect it. This study aims to determine the effect of product prices and quality on the interest of woven fabric buyers in Sukarara Village, Jonggat District, Central Lombok Regency. This research is a field research (field research), using a quantitative approach. The population in this study were all woven fabric consumers in Sukarara Village, Jonggat District, Central Lombok Regency. The sampling method uses judgment sampling with a sample of 50 respondents. Data analysis using multiple linear regression analysis techniques with IBM SPSS 18.0 as an analysis tool. The results of this study indicate that the price variable has a positive and significant effect on buyer interest. This is based on the value of tcount of 3.039 with sig. t is 0.004 (p <0.05). Product quality variables have a positive and significant influence on purchasing decisions. This is seen from the results of the t-test which has a tcount of 3.727 with sig. t is 0.001 (p <0.05). While simultaneously, the variable price and product quality affect buyer interest as evidenced by the results of the F-test which produces a calculated F value of 57.605 with sig. amounting to 0,000 (p <0.05). Then, the contribution of product price and quality variables to purchasing decisions is 71.0% which is seen from the R2 value of 0.710, while the remaining 29% is influenced by other variants outside the model.